Effect of estuarine dam location and discharge interval on estuarine hydrodynamics, sediment dynamics, and morphodynamics - Figueroa, Steven M.; Son, Minwoo; Lee, Guan-hong (Frontiers in Marine Science, 2022)
The effect of an estuarine dam located near the mouth for a range of estuarine types (strongly stratified, partially mixed, periodically stratified, and well-mixed) has been studied using a numerical model of an idealized estuary. However, the effect of different dam locations and freshwater discharge intervals has not yet been studied. Here, models were run for each estuary type with dam locations specified at x = 20, 55, and 90 km upstream from the mouth, and discharge intervals specified as once every Δt = 0.5, 3, and 7 days. The hydrodynamic, sediment dynamic, and morphodynamic results for the pre- and post-dam estuaries were analyzed to understand changes in estuarine processes. It was found that the estuarine dam altered the tide and river forcing in turn altering the stratification, circulation, sediment fluxes, and depths. The estuarine dam location primarily affected the tide-dominated estuaries, and the resonance length was an important length scale affecting the tidal currents and Stokes return flow. When the location was less than the resonance length, the tidal currents and Stokes return flow were most reduced due to the loss of tidal prism, the dead-end channel, and the shift from mixed to standing tides. The discharge interval primarily affected the river-dominated estuaries, and the tidal cycle period was an important time scale. When the interval was greater than the tidal cycle period, notable seaward discharge pulses and freshwater fronts occurred. Dams located near the mouth with large discharge interval differed the most from their pre-dam condition based on the estuarine parameter space. Greater discharge intervals, associated with large discharge magnitudes, resulted in scour and seaward sediment flux in the river-dominated estuaries, and the dam located near the resonance length resulted in the greatest landward tidal pumping sediment flux and deposition in the tide-dominated estuaries.